Cooperative promotions in the distribution channel. (March 2015) - Karray, Salma
Abstract: This paper investigates equilibrium strategies for both horizontal (HJP) and vertical (VJP) joint promotions (cooperative advertising) in the supply chain. A game theoretic model is solved for two setups: a centralized channel competing with a decentralized one (DC), and two competing decentralized channels (DD). Retailers decide of HJP and regular promotional efforts, as well as of prices. Manufacturers choose their transfer prices and VJP support rates offered to the retailer. For each setup, we solve for equilibrium strategies in two games: when retailers invest in HJP, and when they do not. Comparison of equilibrium solutions shows that, for both DC and DD settings, the manufacturer׳s VJP support to the retailer would be affected differently by HJP depending on the levels of both price and promotional competition. In particular, manufacturers should offer a lower VJP rate when price competition is lower than promotional competition, and higher VJP rates otherwise. The effects of HJP on equilibrium profits depend on the channel structure. When a decentralized channel is competing with a centralized one, we find that HJP is beneficial to the manufacturer. However, it can be detrimental to the decentralized retailer׳s profits, especially when products are closely competing both on prices and promotions but HJP is not highly effective. It can also harm the centralized channel if it has the highest baseline demands in the market. This result is not supported in case of similar competing decentralized channels, for which HJP leads to higher equilibrium profits earned by each retailer and manufacturer. Abstract : Highlights: We study horizontal (HJP) and vertical (VJP) joint promotions in competing channels. Retailers׳ HJP with decentralized and centralized structured partners is considered. The profitability of HJP depends on the structure of the partnering channel. HJP leads to changes in VJP rates that depend on competition levels.